Arab women writers : an anthology of short stories - Cohen-Mor, Dalya, 1948- (Albany, NY : State University of New York Press, 2005)
"Consisting of sixty short stories by forty women writers from across the Arab world, this collection opens numerous windows onto Arab culture and society and offers keen insights into what Arab women feel and think. The stories deal not only with feminist issues but also with topics of a social, cultural, and political nature. Different styles and modes of writing are represented, along with a diversity of techniques and creative approaches, and the authors present many points of view and various ways of solving problems and confronting situations in everyday life. Lively, outspoken, and provocative, these stories are essential reading for anyone interested in the Arab world."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Arab women writers: a brief sketch -- Thematic aspects -- Modes of writing -- Arab women: old images, new profiles -- That summer holiday / Samiya At'ut -- The parting gift / Umayma al-Khamis -- Let's play doctor / Nura Amin -- In the moonlight / Radwa Ashour -- At the beach / Buthayna al-Nasiri -- A helping hand / Mona Ragab -- In the recesses of memory / Fawziya Rashid -- Fragments from a life / Sharifa al-Shamlan -- The slave / Najiya Thamir -- The picture / Nawal al-Saadawi -- The picture / Latifa al-Zayyat -- The picture / Layla al-Uthman -- The smile / Nafila Dhahab -- My mother's friend / Nura Amin -- A worthless woman / Hayat Bin al-Shaykh -- Where to? / Colette Suhayl al-Kuri -- The cat / Layla Ba'labakki -- The woman of my dreams / Fadila al-Faruq -- Mozart's fez / Samiya At'ut -- A virgin continent / Samira Azzam -- An old couple / Nadiya Khust -- A mistake in the knitting / Ihsan Kamal -- My wedding night / Alifa Rifaat -- The dummy / Sahar al-Muji -- The cat, the maid, and the wife / Daisy al-Amir -- Sun, I am the moon / Hanan al-Shaykh -- The dreadful sea / Zuhur Wanisi -- Woman with a story / Mayy Ziyada -- The Persian rug / Hanan al-Shaykh -- The dream / Aliya Mamdouh -- Pharaoh is drowning again / Sakina Fuad -- The spider's web / Ihsan Kamal -- Man and woman / Rafiqat al-Tabi'a -- Heir apparent / Ramziya Abbas al-Iryani -- The newcomer / Daisy al-Amir -- International women's day / Salwa Bakr -- The filly became a mouse / Layla Ba'labakki -- Restoration ; Waiting for Hayla / Umayma al-Khamis -- The closely guarded secret / Sahar al-Muji -- I will never forfeit my right / Mona Ragab -- Homecoming / Fadila al-Faruq -- Bittersweet memories / Zabya Khamis -- Tears for sale / Samira Azzam -- Misfortune in the alley / Ramziya Abbas al-Iryani -- Questioning / Fawziya Rashid -- The dinosaur / Emily Nasrallah -- Moonstruck / Hadiya Sa'id -- A moment of truth / Khayriya al-Saqqaf -- The future / Daisy al-Amir -- The gallows / Suhayr al-Tall -- The breeze of youth / Ulfat al-Idilbi -- A successful woman / Suhayr al-Qalamawi -- In need of reassurance / Radwa Ashour -- Short and sassy / Nafila Dhahab -- The collapse of barriers / Samiya At'ut -- The beginning / Salwa Bakr -- A moment of contemplation / Nuzha Bin Sulayman -- I will try tomorrow / Mona Ragab.
Translated from the Arabic.
Includes bibliographical references (pages 291-295).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Short stories, Arabic -- Translations into English; Arabic fiction -- Women authors -- Translations into English; Nouvelles arabes -- Anthologies -- Traductions anglaises; Écrits de femmes arabes -- Traductions anglaises; LITERARY CRITICISM -- African; Arabic fiction -- Women authors; Short stories, Arabic; Translations